2003
DOI: 10.1002/elan.200390062
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Properties of Electropolymerized Ni(II)curcumin Complex

Abstract: The voltammetric behavior in alkaline solution of a nickel-based chemically modified electrode (poly-Ni(II)curcumin) prepared by oxidative electropolymerization of nickel-curcumin complex for electrooxidation of aliphatic alcohols was investigated by cyclic voltammetry and rotating disk technique (curcumin 1,7-bis[4-hydroxy-3-methoxyphenyl]-1,6-heptadiene-3,5-dione). The dependence of the oxidation current on the alcohol concentration and on the number of redox centers Ni(II)/Ni(III) is discussed. From the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 23 publications
(10 reference statements)
2
23
0
Order By: Relevance
“…The continuous cycling increased the current of latter peak, which indicates the formation of conductive poly-Ni(L) film growth on a glassy carbon electrode. The characteristics of the CVs are in very good agreement with those of the literature [19]. The formation of polymeric film suggests a high degree of adherence to the glassy carbon electrode.…”
supporting
confidence: 88%
“…The continuous cycling increased the current of latter peak, which indicates the formation of conductive poly-Ni(L) film growth on a glassy carbon electrode. The characteristics of the CVs are in very good agreement with those of the literature [19]. The formation of polymeric film suggests a high degree of adherence to the glassy carbon electrode.…”
supporting
confidence: 88%
“…Continuous increase in the amplitude of the voltammometric peaks indicate that the Ni-MA film is formed as the number of cycles increased. The same results have been previously reported [32][33][34][35][36][37]. The redox reaction which occurs during cycles are related to the Ni(II)-MA/Ni (III)-MA transition.…”
Section: Resultssupporting
confidence: 87%
“…The catalytic oxidation of methanol on a glassy carbon electrode which was electrochemically modified by a conductive Ni(II)-curcumin complex film was first reported in 1995. 47 In the course of this study, it was found that a glassy carbon electrode modified by this Ni(II)-curcumin film can act as a very effective catalyst for the oxidation of alcohols. Deposition of the nickel(II) curcumin complex was simply performed by contacting the clean electrode surface with a freshly prepared solution of curcumin, a Ni(II) salt and 0.1 M NaOH.…”
Section: Non-medicinal/analytical Applications Of Metal Curcumin Compmentioning
confidence: 90%